Bioactivity of Nonedible Parts of Punica granatum L.: A Potential Source of Functional Ingredients - Nawraj Rummun; Jhoti Somanah; Srishti Ramsaha; Theeshan Bahorun; Vidushi S. Neergheen-Bhujun (International Journal of Food Science)
Punica granatum L. has a long standing culinary and medicinal traditional use in Mauritius. This prompted a comparative study to determine the bioefficacy of the flower, peel, leaf, stem, and seed extracts of the Mauritian P. granatum. The flower and peel extracts resulting from organic solvent extraction exhibited strong antioxidant activities which correlated with the high levels of total phenolics, flavonoids, and proanthocyanidins. The peel extract had the most potent scavenging capacity reflected by high Trolox equivalent antioxidant capacity value ( μmol/g air dry weight), very low IC50 values for hypochlorous acid ( mg air dry weight/mL), and hydroxyl radicals scavenging ( mg air dry weight/mL). Peel extracts also significantly inhibited S. mutans (), S. mitis (), and L. acidophilus () growth compared to ciprofloxacin. The flower extract exhibited high ferric reducing, nitric oxide scavenging, and iron (II) ions chelation and significantly inhibited microsomal lipid peroxidation. Furthermore, it showed a dose-dependent inhibition of xanthine oxidase with an IC50 value of  mg air dry weight/mL. This study showed that nonedible parts of cultivated pomegranates, that are generally discarded, are bioactive in multiassay systems thereby suggesting their potential use as natural prophylactics and in food applications.